2020
DOI: 10.56059/jl4d.v7i1.376
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ICT Competencies Among Distance Learning Students in selected Study Centres of the National Open University of Nigeria

Abstract: The research evaluated the ICT competencies of Distance learning students of the National Open University of Nigeria, as a pre-requisite for their effectiveness in a computer-based learning environment. 186 students (66 males and 120 females) responded to the questionnaire:  Learners’ Competency in the use of ICT (LC in CT), which was adopted from the UNESCO Competency Standard (2008).  Results show that distance learning students of the National Open University of Nigeria show competencies in the use of ICT t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The independent t-test display in Table 7 did not reveal any significant difference between residential status and the test anxiety among pre-service teachers 𝑡(311) = 0.392, 𝑝 = 0.722. With regards to the factors associated with test anxiety among pre-service teachers, the results from the self-reported factors revealed that the most self reported factors are; exam format with (182) students followed by the examiner (137), examination time (74), previous failure (63), not covered much (60), previous success/overexpectation (44), the presence of an invigilator (31), examination theatre (24), and the least being content of the course (9) respectively as shown in Figure 1. This findings contradicts with the factors indentified by Neemati et al [48], who reported environmental and presence of invilator as predictors of test anxiety.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The independent t-test display in Table 7 did not reveal any significant difference between residential status and the test anxiety among pre-service teachers 𝑡(311) = 0.392, 𝑝 = 0.722. With regards to the factors associated with test anxiety among pre-service teachers, the results from the self-reported factors revealed that the most self reported factors are; exam format with (182) students followed by the examiner (137), examination time (74), previous failure (63), not covered much (60), previous success/overexpectation (44), the presence of an invigilator (31), examination theatre (24), and the least being content of the course (9) respectively as shown in Figure 1. This findings contradicts with the factors indentified by Neemati et al [48], who reported environmental and presence of invilator as predictors of test anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, Zeidner [30] postulates that worry and pessimistic thinking, self-criticism, or anxiety about the negative effects of failure that emerge during testing situations, form the cognitive component of test anxiety, while also causing students to 'freeze up' mentally and unable to remember the required information needed to pass a test. Amini and Reamen [31] argued that worry, which is an element of test anxiety, is more consistently connected with decline in academic test scores.…”
Section: Introductionmentioning
confidence: 99%